The unique and synergistic effects of social isolation and loneliness on 20-years mortality risks in older men and women - Marja Aartsen; Hanna Vangen; George Pavlidis; Thomas Hansen; Iuliana Precupetu; Iuliana Precupetu (Frontiers Media S.A., 2024)
IntroductionThis study investigates the individual and combined impacts of loneliness and social isolation on 20-year mortality risks among older men and women.MethodsUtilizing data from the Norwegian Life Course, Ageing, and Generation study (NorLAG) carried out in 2002, 2007 and 2017, we assessed loneliness via direct and indirect questions, and social isolation through factors like partnership status and contact frequency with family and friends. Yearly information on mortality was derived from the national registries and was available until November 2022. Gender-stratified Cox regression models adjusted for age and other risk factors were employed.ResultsOf the 11,028 unique respondents, 9,952 participants were included in the study sample, 1,008 (19.8%) women and 1,295 (26.6%) men died. In the fully adjusted models including indirectly assessed loneliness, social isolation increased the 20-year mortality risk by 16% (HR = 1.16, 95% CI 1.09-1.24) for women and 15% (HR = 1.15, 95% CI 1.09-1.21) for men. This effect was primarily driven by the absence of a partner and little contact with children for both genders. Loneliness measured with indirect questions lost its significant association with mortality after adjusting for social isolation and other factors in both genders. However, for men, reporting loneliness via a direct question was associated with a higher mortality risk, even in the fully controlled models (HR = 1.20, 96% CI 1.06-1.36). Interactions between loneliness and social isolation were not, or only borderline significantly, associated with mortality risks in the fully controlled models.DiscussionSocial isolation, but not loneliness measured with indirect questions are associated with a 15-16% higher mortality risk in both men and women. However, loneliness assessed with a direct question is associated with increased mortality in men, even after controlling for social isolation and other relevant factors, which might suggest that men may deny loneliness, unless it is (very) severe. These findings emphasize the importance of methodological precision in the measurement of loneliness and social isolation.